Diagnostic value of high resolution ultrasound in localisation of the undescended testis in children - Opeoluwa A Adesanya; Adesoji O Ademuyiwa; Christopher O Bode; Adekunle A. O. Adeyomoye (Wolters Kluwer Medknow Publications, 2013)
Background: The use of ultrasonography in the pre-operative localisation of undescended testes has become controversial due to fears about its accuracy. This study was designed to ascertain the accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of ultrasonography in the localisation of the undescended testes in children. Patients and Methods: A prospective evaluation of all boys undergoing operation for undescended testes at the Lagos University Teaching Hospital, Idi-Araba, Lagos, over a 12 month period was performed. The pre-operative clinical and ultrasound findings were compared with the findings on surgical exploration. Results: Forty boys with 52 undescended testes were studied. The mean age of the boys at the time of surgery was 4.0 ± 0 years (range 1-11 years). Forty-six (88.5%) testes were localised pre-operatively by ultrasound- 20 of 22 (90.9%) palpable testes and 26 of 30 (86.7%) non-palpable testes. Intra-operatively, 49 (94.2%) of the undescended testes were found while 3 (5.8%) were absent/vanishing testes. Ultrasound evaluation had an accuracy of 86.5%, sensitivity of 89.8%, and specificity of 33.3%, PPV of 95.7% and a NPV of 16.7%. Conclusion: Ultrasound assessment is beneficial in pre-operative evaluation of children with undescended testes.